Enhancing Critical Thinking Skills of Students Related to Temperature and Heat Topics Through Problem Solving- Laboratory Model - Adam Malik; Yeni Novita; Ade Yeti Nuryantini (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
This study aims to determine the implementation of the learning problem-solving laboratory model and improvement of critical thinking skills of students on temperature and heat topic. The method used in this research was pre-experiment, with one-group pretest-posttest design. The population of this study was class X SMA Muhammadiyah 1 Garut. The sample was selected by random sampling technique, with a sample of one class X-2, amounting to 30 people. The implementation of problem-solving laboratory model learning was observed by observers with observation sheets and improvement of students' critical thinking skills measured by essay tests. The results showed that the average implementation of problem-solving laboratory model learning for teacher activities was 84% and student activities at 80% were both categorized well. There was an increase in the critical thinking skills of students shown by the average of the normalized gain value of 0.64 include the medium category. Thus, the problem-solving laboratory model learning can be used as an alternative in improving students' critical thinking skills on the topic of temperature and heat.